A New, Critical Edition of Armenian Deuteronomy, Forty Years after Its “Diplomatic” Predecessor: Reflections and the Results of New Collations - Cox, Claude E. (Matenadaran, 2024)
Abstract This paper serves to introduce a new critical edition of Armenian Deuteronomy, forty years after the diplomatic edition was prepared as a doctoral thesis at the University of Toronto. It deals with the challenges involved, such as how to reconstruct the underlying Greek source text and linguistic issues that are to be taken into account in collation, notably certain preferences in word order. The last half of the paper advances the rewards that repay the preparation of such a critical edition, including the recovery of an early form of the Greek source text, and, in the case of Deuteronomy, an appreciation of the contribution of the translator in shaping the theological message of the book.
Keywords: collating manuscripts.